The Effect of Skill and Attitude on Performance with Work Effectiveness as an intervening variable at Research and Development Planning Service Bintan - Kurniadi, Didi; Husni, Faisal; Rahmawati, Putri; Kawangung, Verlina Y (International Journal of Psychosocial Rehabilitation, 2020)
The regional government has a vital role in the implementation of the economy. It is Regency government has a vital role in the implementation of the economy. It is necessary to have excellent quality State Civil Apparatus to participate in the implementation of government programs. In particular, the Bintan Research and Development Planning Service which has complex tasks and functions in developing Bintan Regency. The performance of State Civil Apparatus measured by various aspects such as the skills and attitudes of employees, the better the skills and attitudes of employees will increase the effectiveness of work, which will ultimately improve the performance of the employees themselves. This study is to analyze the effect of skills and attitudes on performance, both directly and through work effectiveness. The research methodology uses path analysis using SPSS with a sample of 43 Civil Apparatus in the Bintan Research and Development Planning Service. Research findings explain that skill has a significant effect on the effectiveness and performance directly. While attitude does not significantly influence the effectiveness and performance directly. Based on the indirect effect, it is found that the skills affect the performance through work effectiveness, while the attitude does not affect the performance through work effectiveness.